International Terrorism Using Toxic Chemicals as an Element of Hybrid Warfare - E. N. Glotov; V. P. Kotov; I. A. Lozanov; M. L. Makarov; О. М. Nikitin; А. М. Fleyer; N. I. Shilo (Вестник войск РХБ защиты, 2023)
Modern terrorism is a complex system that consists of a complex of complementary processes – ideological, criminal, military, political, religious and nationalistic. Chemical terrorism is one of the elements of hybrid warfare – a new technology in the fight for the reorganization of the world at the present stage.   The purpose of this article is to consider one of the elements of hybrid wars – chemical terrorism.   Sources and informational basis of the research, methodology. In this work, the sources published by the Organization for the Prohibition of Chemical Weapons (OPCW) were used. The publications available through the databases PubMed, Google Scholar, eLibrary, etc. were also studied. Research method – system analysis. The probability of the use of chemical warfare agents and toxic chemicals by terrorists of various ideological orientations as part of a hybrid war strategy has been studied.   The discussion of the results. Hybrid military conflicts of a non-classical nature involve the participation of international terrorist organizations in hostilities. The Convention on the Prohibition of the Development, Production, Stockpiling and Use of Chemical Weapons and on Their Destruction (CWC) does not explicitly prohibit non-state actors from obtaining and using chemical weapons. This situation is very convenient for the states that have signed the CWC and use terrorist organizations as part of the strategy of indirect action. In such cases the information and psychological operations are aimed at the collapse and fragmentation of countries, undermining their ability to resist, discrediting their leaders, and causing a split in the ranks of the allies. This was most clearly shown in the incidents with the use of toxic chemicals in Syria.   Conclusion. Working groups under the auspices of the UN and the OPCW, sent to Syria to investigate incidents with the use of sarin, proved unable to conduct objective investigations. They usually ended up on the side of the sponsors of chemical terrorist attacks, despite the evidence of falsification. This, in turn, can lead to serious military conflicts, for which the role of casus belli will be played by false news from the global media. The only mechanism that made it possible to stop such provocations in Syria was a public warning from the Russian side about the place and time of the planned false flag attack. At the same time, such a selective position of the UN and the OPCW can at any moment lead to the loss of the control over chemical weapons in certain regions of the world.